Matrix metalloproteinase-9 might affect adaptive immunity in non-ST segment elevation acute coronary syndromes by increasing CD31 cleavage on CD4+ T-cells. (2nd December 2017) - Angelini, Giulia; Flego, Davide; Vinci, Ramona; Pedicino, Daniela; Trotta, Francesco; Ruggio, Aureliano; Piemontese, Giuseppe P; Galante, Domenico; Ponzo, Myriana; Biasucci, Luigi M; Liuzzo, Giovanna; Crea, Filippo
Abstract: Aims: In patients with acute coronary syndrome (ACS), the higher activity of effector T-cells suggests that mechanisms involving adaptive immunity dysregulation might play a role in coronary instability. The shedding of the functional CD31 domain 1–5 leads to uncontrolled lymphocyte activation. In experimental models, matrix metalloproteinase-9 (MMP-9) has been implicated in endothelial CD31 cleavage. Interestingly, higher serum levels of MMP-9 have been observed in ACS. We aim to investigate the mechanisms underlying CD31 dysregulation in ACS. Methods and results: To assess CD31 cleavage on CD4+ T-cells, we analysed by flow cytometry CD4+ T-cells of 30 ACS, 25 stable angina (SA) patients, and 28 controls (CTRL) using two different CD31 antibodies that specifically recognize domain 1–5 or the non-functional membrane-proximal domain 6. The ratio between the domains was significantly lower in ACS than in SA and CTRL ( P  = 0.002 ACS vs. SA; P  = 0.002 ACS vs. CTRL). After stimulation with anti-CD3/CD28, the 1–5/6 domain ratio was significantly lower in ACS than in SA ( P  = 0.005). ELISA of supernatants obtained from T-cell receptor-stimulated CD4+ T-cells showed higher production of MMP-9 in ACS than in SA ( P  < 0.001). CD31 domain 1–5 expression in activated CD4+ T-cells from ACS patients increased after treatment with a specific MMP-9 inhibitor ( P  = 0.042). Conclusion: Our study suggest that enhanced MMP-9 release plays a key role in determining the cleavage and shedding of the functional CD31 domain 1–5 in CD4+ T-cells of ACS patients. This mechanism might represent an important therapeutic target to modulate T-cell dysregulation in ACS.